Evaluation of the Antibiofilm Efficacy of Sodium Hypochlorite Combined with Green-Synthesized Silver Nanoparticles Against Enterococcus faecalis - An Invitro Study - Krishnan, Aruna; Bhandari, Sarita (Journal of Neonatal Surgery, 2025)
Background: Enterococcus faecalis biofilms contribute significantly to endodontic treatment failure. Sodium hypochlorite (NaOCl), though effective, presents cytotoxicity at higher concentrations. Green-synthesized silver nanoparticles (AgNPs) offer a promising adjunct for safer and more effective disinfection. The aim of the study is to assess and compare the antibiofilm efficacy of NaOCl alone and in combination with AgNPs synthesized using Ficus religiosa bark extract against E. faecalis biofilms. Methods: F. religiosa extract was prepared and used for the green synthesis of AgNPs using 1 mM AgNO₃. Synthesized nanoparticles were characterized and incorporated with NaOCl. A microtiter plate assay assessed antibiofilm activity against E. faecalis across serial concentrations (3% to 0.09%). Biofilm inhibition was quantified using crystal violet staining and optical density at 570 nm. Statistical significance was evaluated using one-way ANOVA with Tukey’s post-hoc test (p < 0.05). Results: The NaOCl + AgNP formulation demonstrated significantly higher antibiofilm activity than NaOCl alone at all tested concentrations (p < 0.05). At 0.09%, the combination achieved 42.44% inhibition compared to 9.91% with NaOCl alone, indicating enhanced efficacy even at minimal concentrations. Conclusion: Combining NaOCl with F. religiosa-mediated AgNPs markedly improves antibiofilm performance against E. faecalis. This biogenic nanoparticle approach offers a safer, more effective strategy for root canal disinfection and could reduce reliance on higher concentrations of NaOCl.